Respuesta :

First, assume Alex is X years old and that Emma is Y years old. 

Since Alex is 6 years older than Emma, it means X - 6 = Y. 

Since the sum of their ages is 32, it means X + Y = 32. 

Substitute the Y in the second equation with X - 6 to get X + (X-6) = 32. This is simplified to 2X - 6 = 32 or 2X = 38. Solving the equation for X gets that X = 19. 

This means Alex is 19.
Let Emma= e, Alex= 6+e because he is 6 years older than Emma. Since their sum is 32, you would add e+(6+e)=32 and solve for e.  

e+(6+e)=32
6+2e=32
2e=32-6
2e=26
e=26/2
e=13
So Emma is 13, Alex is 13+6=19 years old.